Kinerja Pegawai Kecamatan Sigaluh Dalam Pembangunan Aplikasi Sigaluh Belajar (SIBELA) Di Kecamatan Sigaluh Kabupaten Banjarnegara - Tutus Liyanto (Praxis : Jurnal Sains, Teknologi, Masyarakat dan Jejaring, 2021)
A village is a spearhead for the development in Indonesia. It has an important role in every aspect of the development. Moreover, a development that have direct touch and effect to the citizen. The government of Indonesia has enforced the Decree No. 6 of 2014 on The Village.  It stated that village has the autonomy to run and manage their own household. One of the consequences is that the chief of the village and his/her officials have to have excellent working performance. The purpose of this research is to know the Sigaluh Sub-District officials’ working performance on the development of Sibela Application. Sibela is the abbreviation of  Sigaluh Belajar. It is an application to help the Sigaluh Sub-District officials to learn. The data collection used is observation, interview and literature study. Observation was done to the 127 Sigaluh Sub-District officials. The data sampling technique used was purposive sampling method, while the research method is qualitative method. Sibela was made by using open source Modular Object-Oriented Dynamic Learning Environment (Moodle). It is commonly used by education institution as an application for long distance learning. It can be use and develop as needed. It is also an open source application under GNU license. The result of this research shows that on the development of the Sibela Application, the Sigaluh Sub-District officials have an excellent performance and team work.